Rules versus Discretion in Public Service: Teacher Hiring in Mexico - Estrada, Ricardo (Journal of Labor Economics, 2019)
This paper compares the performance of teachers hired on the basis of a standardized exam to those hired at the union’s discretion in Mexico. My results show that the discretionary hires perform considerably worse than the rule-based hires (as measured by value added to student achievement). The evidence presented here shows the impact of personnel selection mechanisms on the quality of public service delivery.